Brands, Truthiness and Post-Fact: Managing Brands in a Post-Rational World. (June 2018) - Berthon, Pierre R.; Pitt, Leyland F.
In the past US election cycle, and mirrored by similar events in Europe, two trends have come to dominate social discourse: truthiness (the validity of something based on how it feels) and post-fact (taking a position that ignores facts). Human discourse has always contained elements of these, but the nature of the Internet and social media has pushed truthiness and post-facts to new levels. The purpose of this paper is to explore the complicated relationship brands have with fake news and discuss the implications for brand management of a post-truth world. We explore the complicated relationship brands have with fake news: Brands both fuel fake news and are burned by it. Next, we turn to the intellectual and instrumental roots of the post-truth world: postmodernism and its technological enablers, show how marketing became a purveyor of the postmodern worldview, and how brands have increasingly adopted truthiness and post-fact positions. We offer managers a way out of the postmodern cul-de-sac, discussing ways brands can be rethought and managed in a post-rational world.